Impact of admission blood glucose levels on prognosis of elderly patients with ST elevation myocardial infarction treated by primary percutaneous coronary intervention - Ekmekci, Ahmet; Uluganyan, MAHMUT; ULUGANYAN, MAHMUT; Tufan, Fatif; Uyarel, Huseyin; Karaca, Gurkan; Kul, Seref; Gungor, Baris; Ertas, Gokhan; Erer, Betul; Sayar, Nurten; Gul, Mehmet; et al. (My University, 2013)
Objective: Admission hyperglycemia in acute myocardial infarction (MI) is related with increased in-hospital and long term mortality and major cardiac adverse events. We aimed to investigate how admission hyperglycemia affects the short and long term outcomes in elderly patients (> 65 years) after primary percutaneous coronary intervention for ST elevation myocardial infarction. Methods: We retrospectively analyzed 677 consecutive elderly patients (mean age 72.2 ± 5.4). Patients were divided into two groups according to admission blood glucose levels. Group 1: low glucose group (LLG), glucose < 168 mg/dL; and Group 2: high glucose group (HGG), glucose > 168 mg/dL. Results: In-hospital, long term mortality and in-hospital major adverse cardiac events were higher in the high admission blood glucose group (P < 0.001). Multivariate regression analysis showed: Killip > 1, post-thrombolysis in MI < 3 and admission blood glucose levels were independent predictors of in-hospital adverse cardiac events (P < 0.001). Conclusions: Admission hyperglycemia in elderly patients presented with ST elevation myocardial infarction is an independent predictor of in-hospital major adverse cardiac events and is associated with in-hospital and long term mortality.
Keywords: In-hospital mortality; Admission hyperglycemia; Elderly patients; Long-term mortality; Major adverse cardiac events